THE EFFECTIVENESS OF INDONESIA’S SHARIA ECONOMIC DIPLOMACY IN PENETRATING INTERNATIONAL HALAL TRADE BARRIERS - Akhmad Andri Firdaus (Gunung Djati Conference Series, 2025)
This article explores how Indonesia utilizes sharia-based economic diplomacy to navigate obstacles in the international halal trade arena. Positioned as a vital tool, sharia economic diplomacy supports the nation's strategy to broaden access for Indonesian halal goods in the face of substantial tariff and non-tariff hurdles, including certification issues, standard compliance, and protectionist tendencies from importing nations. Initiatives led by the Ministry of Foreign Affairs in tandem with the Halal Product Assurance Agency (BPJPH) highlight the necessity of cohesive inter-institutional efforts to boost the global appeal of Indonesian halal exports. As the world’s most populous Muslim-majority nation, Indonesia envisions itself as a central player in the halal industry, yet it grapples with persistent difficulties such as trade imbalances in halal goods and the limited global validation of its halal certificates. Through its diplomatic channels, Indonesia engages in both multilateral frameworks like the OIC and bilateral efforts with key partners, advancing through trade easing measures, international halal fairs, and mutual recognition agreements. The findings show that sharia economic diplomacy can open doors to emerging halal markets, fortify Indonesia’s stance in setting halal benchmarks, and support international regulatory alignment. Nonetheless, its success relies heavily on synchronized actions across government agencies, industry actors, and certifying institutions, alongside responsiveness to shifting trade landscapes. Strengthening this flexible and cooperative diplomatic approach enhances Indonesia’s ability to more effectively and sustainably dismantle global halal trade barriers.